Perilaku Pemustaka Dalam Penelusuran Informasi di Perpustakaan Politeknik Wilmar Bisnis Indonesia - Ummu Khoiriah Lubis; Febi Fadila; Lisa Arlinda; Indah Lestari; Franindya Purwaningtyas (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Information seeking behavior occurs because of a person's perceived need for information. This need can be caused by pressure from outside, such as tasks that must be completed, or because of other factors. The purpose of this research is to find out the behavior of users in searching for information at the Wilmar Bisnis Indonesia Polytechnic library, which uses qualitative research methods. The information search technique applied at the Wilmar Bisnis Indonesia Polytechnic Library is an information search technique by asking directly to the librarian, through the collection shelves in the library, through the internet that has been provided by the library, through the OPAC (online public access catalog), through the collections provided by the library. provided by the library of the Wilmar Bisnis Indonesia Polytechnic to meet the information needs of users. Keywords: User Behavior, Information Search and Libraries